2017
DOI: 10.1007/s12017-017-8446-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Receptor-Related Protein-1 (LRP1) C4408R Mutant Promotes Amyloid Precursor Protein (APP) α-Cleavage in Vitro

Abstract: Previous studies have demonstrated that the low-density lipoprotein (LDL) receptor-related protein-1 (LRP1) plays conflicting roles in Alzheimer’s disease (AD) pathogenesis, clearing β-amyloid (Aβ) from the brain while also enhancing APP endocytosis and resultant amyloidogenic processing. We have recently discovered that coexpression of mutant LRP1 C-terminal domain (LRP1-CT C4408R) with Swedish mutant amyloid precursor protein (APPswe) in Chinese hamster ovary (CHO) cells decreases Aβ production, while also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Recent studies have identified numerous proteins that can regulate APP processing by modulating protein trafficking. For example, low-density lipoprotein receptor-related protein 1 (LRP1), an AD risk factor, is able to enhance APP endocytosis, leading to increased Aβ and sAPPβ generation [ 41 ], whereas mutation of LRP1 increases sAPPα secretion in vitro [ 42 , 43 ]. Another AD risk factor sortilin-related receptor containing LDLR A repeats (SORLA) can bind and sequester APP in intracellular compartments to reduce Aβ production [ 44 ].…”
Section: Aβ and Ad Pathogenesismentioning
confidence: 99%
“…Recent studies have identified numerous proteins that can regulate APP processing by modulating protein trafficking. For example, low-density lipoprotein receptor-related protein 1 (LRP1), an AD risk factor, is able to enhance APP endocytosis, leading to increased Aβ and sAPPβ generation [ 41 ], whereas mutation of LRP1 increases sAPPα secretion in vitro [ 42 , 43 ]. Another AD risk factor sortilin-related receptor containing LDLR A repeats (SORLA) can bind and sequester APP in intracellular compartments to reduce Aβ production [ 44 ].…”
Section: Aβ and Ad Pathogenesismentioning
confidence: 99%
“…In addition, this abnormal aggregation is induced by the impairment of protein regulation systems, such as the endoplasmic reticulum system, ubiquitin-proteasome system (UPS), and autophagy-lysosomal pathway (ALP) 69 . Importantly, dysfunction of several regulating proteins, such as LRP1 70 , SNX6 71 , GGA3 72 , and SORLA 73 affect APP endocytosis, endosomal trafficking, and Aβ production, which are closely associated with the onset of AD.…”
Section: Current Understanding Of Neurodegenerative Diseasesmentioning
confidence: 99%